A potential diagnostic pitfall: Primary synovial sarcoma of the central nervous system - Tauziede-Espariat, Arnault; Macagno, Nicolas; Pissaloux, Daniel; Figarella-Branger, Dominique; Appay, Romain; Bochaton, Dorian; Tazi, Sanaa; Kauv, Paul; Hasty, Lauren; Métais, Alice; Chrétien, Fabrice; Varlet, Pascale (Free Neuropathology, 2022)